Role of Autofluorescence in Inflammatory/Infective Diseases of the Retina and Choroid. (1st April 2014) - Samy, Ahmed; Lightman, Sue; Ismetova, Filis; Talat, Lazha; Tomkins-Netzer, Oren
Abstract : Fundus autofluorescence (FAF) has recently emerged as a novel noninvasive imaging technique that uses the fluorescent properties of innate fluorophores accumulated in the retinal pigment epithelium (RPE) to assess the health and viability of the RPE/photoreceptor complex. Recent case reports suggest FAF as a promising tool for monitoring eyes with posterior uveitis helping to predict final visual outcome. In this paper we review the published literature on FAF in these disorders, specifically patterns in infectious and noninfectious uveitis, and illustrate some of these with short case histories.